2012
DOI: 10.1158/1078-0432.ccr-11-1389
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Digoxin Use and Estrogen-Sensitive Cancers—Risks and Possible Therapeutic Implications

Abstract: Digoxin, a phyto-estrogen, binds with estrogen receptors (ER) and can cause gynecomastia. Among women currently using digoxin, breast and uterus cancer incidences are significantly increased (approximate risk ratios, 1.3-1.5). Both cancers are often estrogen sensitive. In contrast, ovary and cervix cancers are relatively estrogen insensitive, and incidence is unaffected by digoxin exposure. When digoxin use stops, incidence rapidly reverts to that in nonusers. These patterns parallel those of estrogen, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 58 publications
1
49
1
Order By: Relevance
“…Piceatannol has been reported to act as a receptor antagonist in breast cancer cells, via its estrogen-like activity (57). However, the mode of action of piceatannol is likely to be different in ovarian cancer cell lines because breast cancers (and uterine cancers) are often estrogen-sensitive, whereas ovarian and cervical cancers are relatively estrogen-insensitive (58). The Drp1-dependent increases in mitochondrial fission observed point to the possible involvement of its regulator, the calcium-dependent phosphatase calcineurin.…”
Section: Discussionmentioning
confidence: 99%
“…Piceatannol has been reported to act as a receptor antagonist in breast cancer cells, via its estrogen-like activity (57). However, the mode of action of piceatannol is likely to be different in ovarian cancer cell lines because breast cancers (and uterine cancers) are often estrogen-sensitive, whereas ovarian and cervical cancers are relatively estrogen-insensitive (58). The Drp1-dependent increases in mitochondrial fission observed point to the possible involvement of its regulator, the calcium-dependent phosphatase calcineurin.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have shown increases in breast and uterus cancer probably related to estrogenic effects of digoxin (1). A recent large UK study reported a 40% increase in colorectal cancer risk in digoxin users (2), which the researchers suggest possibly reflects direct effects of the sodium potassium ATPase pump on tumorigenic pathways such as the Src/MAPK (3).…”
Section: Introductionmentioning
confidence: 99%
“…Digoxin is a phyto-estrogen [1] used to treat heart failure and supra-ventricular arrhythmias (atrial fibrillation/flutter) [2]. Early animal studies indicate that digoxin may bind to estrogen receptors (ER) [1] and have estrogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Early animal studies indicate that digoxin may bind to estrogen receptors (ER) [1] and have estrogenic effects. In support of this digoxin is a recognized cause of gynecomastia [3], and digoxin use has been associated with increased risk of estrogen-sensitive cancers such as uterus cancer [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation